Penguatan Kepala Satuan Pendidikan dalam Supervisi Akademik Berbasis Refleksi Guru melalui Pendekatan Coaching TIRTA: Sebuah Kegiatan Pengabdian kepada Masyarakat - Nailul Ulah Al Chumairoh Machfud; Dwi Astutiek; Agus Setyawanto; Abdul Quddus Salam; Asyhari; Miftakul Arief (BAMALA Institute, 2025)
This Community Service (PkM) program aims to enhance the capacity of school principals in conducting academic supervision that promotes teacher reflection and professional growth. TIRTA coaching (Target – Identification – Action Plan – Responsibility) was introduced as a reflective framework to guide teachers after supervision. Through the workshop, participants gained both conceptual understanding and practical skills in implementing TIRTA coaching as a follow-up to academic supervision. The results show that school principals became more capable of facilitating teacher reflection and guiding them toward concrete and accountable action plans. This approach strengthens the role of supervision not merely as a form of control, but as a developmental and supportive process to improve teaching quality. The activity is expected to serve as a replicable and sustainable training model for various educational institutions.